Low-intensity resistance training improves flow-mediated dilation in young Hispanic adults - Briceño Torres, José Miguel (2023)
Low-intensity resistance training improves flow-mediated dilation in young hispanic adults. J Strength Cond Res 37(2): 298–304, 2023—The purpose of this study was to compare the effects of 2 resistance exercise training (RET) intensities on brachial artery flow-mediated dilatation (FMD) in sedentary males. Thirty-four men (age = 20.6 ± 1.8 years, height = 171.3 ± 5.2 cm, body mass = 65.2 ± 10.6 kg, and DXA fat mass = 22.3 ± 7.4%) were randomly assigned to a control group (no exercise CTRL, n = 12), RET at 50% of 1 repetition maximum (1RM) (RET50%, n = 12), and RET at 80% 1RM (RET80%, n = 10). The RET program was performed twice per week for 8 weeks; subjects performed the same RET exercises at similar total workloads (1920 arbitrary units [AUs] for the RET80% and 1950 AUs for the RET50%). The FMD% was measured before and after 8 weeks by ultrasound. Mixed factorial analysis of variance (3 groups × 2 measurements), effect size (ES), and 95% confidence intervals (95% CIs) were computed for FMD%. The level of significance was set at p ≤ 0.05. A significant increase (p = 0.001) was found on post-test FMD% in RET50% (mean = 9.9 ± 3.7%, ES = 1.9, and 95% CIs = 2.8–0.9) compared with CTRL (mean = 5.7 ± 1.7%, ES = 0.2, and 95% CIs = −0.4 to 0.8), and there were no significant differences found between RET50% and RET80% and between RET80% and CTRL. Results support the concept of training specificity and provide preliminary evidence that lower resistance and higher repetition RET elicit greater short-term reduced endothelium dysfunction than higher intensity RET at similar training volume.